Gender Construction at Islamic Poor Community: Study of Critical Ethnography in Sidosermo Dalam Surabaya - Ahmad Ridwan; Muhammad Faruki (University of Muhammadiyah Malang, 2024)
This study focuses on studying gender construction in the Islamic community in Surabaya. This community is in Kampung Sidosermo Dalam, one of the Islamic area in Surabaya. In everyday social and cultural conditions, women always wear the hijab and men wear koko shirts and sarongs. Women are always constructed as the second social class below men. The social construction that is built is not only agreed upon by men, but women also agree on it. The motto that women live by every day is suwargo nunut neroko katut. That a woman's heaven and hell is with her husband. The aim of the research is to dismantle unfair gender constructions so that hopefully there will be enlightenment leading to correct gender constructions. The research method uses qualitative with a critical ethnographic approach. The data collection technique used in-depth interviews for 15 informant with Sidosermo Dalam figures, kyai, nyai, RT, RW, as well as women who agreed that they were always in the second class. Apart from that, researchers also used participant observation techniques to explore data. The research results show that women have always experienced oppression since childhood. Every day they receive different treatment from men. The doctrine that women are always subordinate to men has been taught to the population from generation to generation. The construction of suwargo nunut neroko katut becomes a guide for interaction. This social construction is built and maintained using religious arguments as legitimacy. This patriarchal and oppressive condition must be immediately changed and corrected by the government, mass organizations and citizens themselves.